2010
DOI: 10.1007/s00276-010-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

The study techniques of Asian, American, and European medical students during gross anatomy and neuroanatomy courses in Poland

Abstract: The findings highlight the differences in study techniques among students from different ethnic backgrounds. The study approaches used in order to accomplish learning objectives was affected by cultural norms that influenced each student group. These differences may be rooted in technological, religious, and language barriers, which can shape the way MS approach learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
3
20
0
1
Order By: Relevance
“…). Others have similarly reported that medical students ranked CAL resources such as software and websites lower than F2F teaching methods utilizing dissection, prosection, living and radiological anatomy, and didactic lectures (Azer and Eizenberg, ; Kerby et al, ; Zurada et al, ; Johnson et al, ; Davis et al, ; Stirling and Birt, ). This study extends these findings from the classroom setting into the SDS realm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Others have similarly reported that medical students ranked CAL resources such as software and websites lower than F2F teaching methods utilizing dissection, prosection, living and radiological anatomy, and didactic lectures (Azer and Eizenberg, ; Kerby et al, ; Zurada et al, ; Johnson et al, ; Davis et al, ; Stirling and Birt, ). This study extends these findings from the classroom setting into the SDS realm.…”
Section: Discussionmentioning
confidence: 99%
“…Computer‐assisted learning (CAL) resources have been incorporated into anatomy curricula (Azer and Eizenberg, ; Rizzolo et al, ) including in the dissection laboratory (Mayfield et al, ), or used extramurally, providing flexibility in the time, place, and tempo of learning (Johnson et al, ). Studies of medical students' preferences for teaching and learning activities (TLA) and resources in gross anatomy highlight that “traditional” resources such as dissection, prosected specimens, lectures, surface and radiological anatomy, textbooks, and atlases are generally preferred over CAL resources (Azer and Eizenberg, ; Kerby et al, ; Zurada et al, ; Johnson et al, ; Davis et al, ; Olowo‐Ofayoku and Moxham, ). For example, students rated six teaching methods for their suitability to meet several learning objectives (e.g., anatomical information, anatomical variation, 3D visualization, background for clinical disciplines, and developing team skills); overall, dissection rated highest, followed by prosections, living and radiological anatomy, didactic teaching, technology (CAL), and anatomical models (Kerby et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, clarity has been lacking with regards to the preferred pedagogy to be employed (Heylings, ). Although study with human cadaveric material might have been traditionally considered closer to clinical medicine (Zurada et al, ), a nonsystematic review on the transformations in neuroanatomy teaching methodologies has shown that the majority of institutions have been using electronic tools effectively to demonstrate the topography and spatial relationships of neuroanatomical structures to the students (Sotgiu et al, ). For instance, the usage of a neurology case‐based web‐resource showed significant improvement in assessment score of medical students at Oxford University (Svirko and Mellanby, ).…”
Section: Discussionmentioning
confidence: 99%
“…This group was undoubtedly studying this material using several meansdlecture notes, atlases, dissections, and prosections (Zurada et al, 2011)din preparation for their exam. Since we aimed for high external validity by implementing the study aids over a long term and in the students' natural environment, we cannot include the influence of other studying methods in our analyses.…”
Section: Game Design Makes Learning More Predictable By Enhancing Thementioning
confidence: 99%